Electronically tunable MOSFET-only current-mode biquad filter - ÖZENLİ, DENİZ (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2017)
A novel current mode MOSFET-only structure with multi-input single-output (MISO) is proposed. The proposed circuit is free from passive circuit elements like resistors and capacitors and able to realize low-pass (LP), band-pass (BP), high-pass (HP), band-stop (BS) and all-pass (AP) filter functions with using the same circuit configuration. It is also important to note that the proposed filter has electronic tunability property. The proposed circuit is laid-out in the Cadence environment using 0.18 mu m TSMC CMOS technology parameters. The layout area is only 408 mu m(2) and the power consumption is about 0.6 mW. Furthermore, to investigate the performance of the BP filter output of the proposed MISO filter, Monte Carlo and corner analyses are also presented. It is shown that the mismatches and the process variations cause only small deviations for the BP filter configuration. Furthermore, the noise performance of the proposed filter is also investigated. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Current mode filter; Multi-input single-output; Electronically tunable; MOSFET-only; Analog filter design; Analog integrated circuit; CURRENT-CONTROLLED CONVEYORS; GROUNDED CAPACITORS; ALLPASS FILTERS